Thermostable Insensitive Energetic Materials Based on a Triazolopyridine Fused Framework with Alternating Nitro and Amine Groups - Ran, You; Xia, Honglei; Song, Siwei; Wang, Kangcai; Zhang, Qinghua (Synlett, 2023)
In this work, we designed and synthesized a series of novel triazolopyridine fused-ring compounds with alternating nitro and amine groups. Three compounds showed remarkable thermal stability at 256, 310, and 294 °C, respectively, and a low mechanical sensitivity [impact sensitivity (IS) = 40 J, friction sensitivity (FS) = 324 N; IS = 35 J, FS = 240 N; and IS > 40 J, FS = 324 N, respectively]. Significantly, two of these compounds exhibited a better detonation performance [detonation velocity (D) = 8200 and 8335 m s–1, Detonation pressure (P) = 25.6 and 27.2 GPa, respectively] than the widely used heat-resistant explosive hexanitrostilbene (HNS; D = 7612 m s–1, P = 24.3 GPa). Additionally, a nitramine derivative displayed a detonation performance (D = 8569 m s–1, P = 31.3 GPa) similar to that of the high-energy explosive RDX. The superior properties of the materials were further confirmed by X-ray diffraction analysis and by several theoretical calculations (ESP, LOL–π, Hirshfeld surfaces, RDG, and NCI analyses). These results indicated that the three compounds might be potential candidates for use as heat-resistant energetic materials.
Keywords: energetic materials; explosives; triazolopyridines; thermal stability